1994
DOI: 10.3354/meps113039
|View full text |Cite
|
Sign up to set email alerts
|

Vertical migration of blue crab Callinectes sapidus megalopae: implications for transport in estuaries

Abstract: Following larval development in coastal waters, postlarvae (megalopae) of the blue crab Callinectes sapidus Rathbun enter inlets and, against the net seaward flow of estuarine waters, move upstream to juvenile habitats. Abundance and vertical distribution of blue crab megalopae in the York River, Virginia, USA, a subestuary of Chesapeake Bay, was quantified to examine the hypothesis that megalopae are not transported simply as passive particles, but display behaviors that augment their immigration. Megalopal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 37 publications
4
52
0
Order By: Relevance
“…Convergent surface currents can carry organisms from either side of a front to the region of downwelling. Swimming against the current would prevent megalopae from being downwelled to deeper depths, and simultaneously allow megalopae to be transported up-estuary during flood tide Although downwelling at frontal zones may not be a stimulus for upward larval swimming behavior several laboratory studies have demonstrated that biachyuran crab larvae exhbit upward swimming behavioi under the type of downwelling conditions which occur at ttdal fronts (see Sulkin 1984 and references therein) Moreover, we found that the mean concentration and flux of megalopae was 6 to 20 times greater, respectively, at the surface than at 3 to 4 m depth Conversely, brachyuran crab larvae sampled along estuarine fronts in Delaware Bay were consistently found below the pycnocline in dense seawater (Clancy & Epifanio 1989) Clancy & Epifanio (1989 postulated that the greater abundance of crab larvae below the pycnocline in Delaware Bay was due to the often deep distnbution of advanced zoeal stages of many estuanne species of crab whose behavior favors retent~on wlthin the estuary (see Sandifer 1975) rather than export and eventual return Our unreplicated neuston measurements during different tldal stages suggest that concentrations of Dungeness crab megalopae In the surface are dramatically higher dunng flood tide than ebb These observations are consistent with predictions based on selective tidal-stream transport up-estuary (De Vries et a1 1994, Olmi 1994) Thls mechanism involves rhythmic increases in swimming activity of megalopae such that they ride flood-tide currents in surface waters, and then return to or near the bottom on ebb tides (e g De Vnes et a1 1994, Olml 1994 and references therem) The hypothesis of vertical migration based upon tidal rhythm (shallow at flood, deep at ebb) suggested by Carnker (1951) has been confirmed for larvae of the xanthid crab Rhithropanopeus harrisli (Cronin & Forward 1983), the blue crab Calllnectes sapidus (Epifanio et a1 1984, De Vnes et a1 1994, and the p e n a e~d shrimp Penaeus duorarum Blue crab megalopae in Delaware Bay were virtually absent from the water column dunng ebblng tide but were found concentrated at vanous depths during floodlng tide (Epifanio et a1 1984) In shallow regions near the mouth of Grays Harbor, transport up-estuary would be enhanced If Dungeness crab megalopae remained on the bottom dunng ebb tide and re-entered the water column dunng flood tide Such a selective tidal stream transport mechanism for Dungeness crab megalopae would likely operate irrespective of the presence or absence of fronts Further measurements are needed to deiine the relative importance of vertlcal migration behavior on transport and settlement patterns of Dungeness crab megalopae since an alternative explanation for the observed paucity of megalopae In fronts during ebb tide may be the lateral diffusion of the convergence (l e dilution of the front) dunng ebb tide Neuston measurements of Dungeness crab megalopae, which were replicated in time and space, indicated that convergent velocities associated with estuarine fronts in Grays Harbor are sufficient to collect buoyant and upward-swimming plankton at the surface. Whether or not the buoyant plume fronts often observed a t the ...…”
Section: Discussionsupporting
confidence: 82%
“…Convergent surface currents can carry organisms from either side of a front to the region of downwelling. Swimming against the current would prevent megalopae from being downwelled to deeper depths, and simultaneously allow megalopae to be transported up-estuary during flood tide Although downwelling at frontal zones may not be a stimulus for upward larval swimming behavior several laboratory studies have demonstrated that biachyuran crab larvae exhbit upward swimming behavioi under the type of downwelling conditions which occur at ttdal fronts (see Sulkin 1984 and references therein) Moreover, we found that the mean concentration and flux of megalopae was 6 to 20 times greater, respectively, at the surface than at 3 to 4 m depth Conversely, brachyuran crab larvae sampled along estuarine fronts in Delaware Bay were consistently found below the pycnocline in dense seawater (Clancy & Epifanio 1989) Clancy & Epifanio (1989 postulated that the greater abundance of crab larvae below the pycnocline in Delaware Bay was due to the often deep distnbution of advanced zoeal stages of many estuanne species of crab whose behavior favors retent~on wlthin the estuary (see Sandifer 1975) rather than export and eventual return Our unreplicated neuston measurements during different tldal stages suggest that concentrations of Dungeness crab megalopae In the surface are dramatically higher dunng flood tide than ebb These observations are consistent with predictions based on selective tidal-stream transport up-estuary (De Vries et a1 1994, Olmi 1994) Thls mechanism involves rhythmic increases in swimming activity of megalopae such that they ride flood-tide currents in surface waters, and then return to or near the bottom on ebb tides (e g De Vnes et a1 1994, Olml 1994 and references therem) The hypothesis of vertical migration based upon tidal rhythm (shallow at flood, deep at ebb) suggested by Carnker (1951) has been confirmed for larvae of the xanthid crab Rhithropanopeus harrisli (Cronin & Forward 1983), the blue crab Calllnectes sapidus (Epifanio et a1 1984, De Vnes et a1 1994, and the p e n a e~d shrimp Penaeus duorarum Blue crab megalopae in Delaware Bay were virtually absent from the water column dunng ebblng tide but were found concentrated at vanous depths during floodlng tide (Epifanio et a1 1984) In shallow regions near the mouth of Grays Harbor, transport up-estuary would be enhanced If Dungeness crab megalopae remained on the bottom dunng ebb tide and re-entered the water column dunng flood tide Such a selective tidal stream transport mechanism for Dungeness crab megalopae would likely operate irrespective of the presence or absence of fronts Further measurements are needed to deiine the relative importance of vertlcal migration behavior on transport and settlement patterns of Dungeness crab megalopae since an alternative explanation for the observed paucity of megalopae In fronts during ebb tide may be the lateral diffusion of the convergence (l e dilution of the front) dunng ebb tide Neuston measurements of Dungeness crab megalopae, which were replicated in time and space, indicated that convergent velocities associated with estuarine fronts in Grays Harbor are sufficient to collect buoyant and upward-swimming plankton at the surface. Whether or not the buoyant plume fronts often observed a t the ...…”
Section: Discussionsupporting
confidence: 82%
“…The Megalopa, in contrast, might be stimulated by cooler temperatures to initiate a landward directed migration (for bohavioural and transport patterns of megalopae see e.g. Little & Epifanio, 1991;Olmi, 1994). This thermally controlled behavioural mechanism, probably in combination with a response to salinity changes, would assure an efficient transport towards the s~.~a in the zoeal stages, and towards shallow coastal lagoons and estuaries in the Megalopa, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Megalopae are abundant near the ocean surface (Smyth 1980, McConaugha et al 1983, Epifanio 1988, Epifanio et al 1989 and are probably transported shoreward by wind-generated surface currents (Epifanio et al 1984, Goodrich et al 1989). Movement up an estuary to the site of metamorphosis to the first crab stage is accomplished by selective tidal stream transport, in which megalopae are in the water column during rising tides at night, but absent at other times (Dittel & Epifanio 1982, Brookins & Epifanio 1985, Mense & Wenner 1989, Little 81 Epifanio 1991, Olmi 1994. This developmental sequence suggests that megalopae do not have a home estuary to which they are preferentially recruited.…”
Section: Introductionmentioning
confidence: 99%